RESEARCH FOR THE STRAIN ENERGY RELEASE RATE OF COMPLEX CRACKS BY USING POINT—BY—POINT CLOSED EXTRAPOLATION APPROACH - 郭茂林 孟庆元 王彪 (Applied mathematics and mechanics, 2003)
A new extrapolation approach was proposed to calculate the strain energy release rates of complex cracks.The point-by-point close method was used to calculate the closedenergy,thus the disadvantage of self-inconsistency in some published papers can be avolded.The disadvantage isthat the closed energy is repeatedly calculated:when closed nodal number alongradial direction is more than two,the displacement of nodes behind the crack tipthat is multiplied by nodal forces,the closed energy has been calculated and the crack tipthat ismultiplied bynodal forces,the closed energy has been calculated and the crack surfaces have been closed,and that closed energyof middle point iscalculated repeatedly.A DCB(double cantilever beam) specimen was calculated and compared with samp results are also obtained for comparct tension specimen,three point bend specimen and single edge cracked specimen.In comparison with theoretical results.the error can be limited within 1 per cent.This method can be extended to analyze the fracture of composite laminates with various delamination cracks.